Self-Regulated Learning and Time Discipline in Increasing Student Thesis Completion Productivity (International Journal of Education and Literature, 2026)
Low student thesis completion productivity is a challenge in higher education, particularly at UIN Palangka Raya. Thesis writing requires self-regulation skills and time discipline to enable students to complete their final assignments effectively and on time. This study aims to analyze the role of self-regulated learning and time discipline in improving the thesis completion productivity of final-year students. The study used a qualitative approach with a case study design of five final-year students who were in the process of completing or had completed their theses. Data collection techniques included in-depth interviews, limited observation, and documentation. The data were then analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that self-regulated learning plays a role in helping students plan goals, control motivation and emotions, and conduct consistent self-evaluation. Time discipline has been proven effective in reducing procrastination through the implementation of daily schedules, prioritization, and distraction management. Therefore, the integration of self-regulated learning and time discipline is an important strategy in increasing the thesis completion productivity of students and supporting sustainable academic success.